A case of non-pueperal chronic uterine inversion managed successfully - Fonseca, Michelle; Desai, Ashwini; Kapote, Deepali; Gawai, Swati; Syed, Anam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Uterine inversion is prolapse of the uterine fundus and corpus turned inside out towards or through the cervix. The non-puerperal type of uterine inversion is a quite rare occurrence and it accounts for only 17% of all uterine inversion cases. We present a case of 45 year old multiparous female who presented to us with polymenorrhagia with fibroid polyp. Ultrasonography confirmed the clinical findings however Intraoperatively examination under anaesthesia revealed uterine inversion. On table we proceeded with Haultains method of uterine reposition followed by total abdominal hysterectomy. Patient recovered well and thus case was successfully managed.